Inflammation promotes erythropoietin induced vascular calcification by activating p38 pathway. Issue 3 (1st March 2022) - Li, Xunjia; Liu, Chengxuan; Li, Ying; Xiong, Weijian; Zuo, Deyu
ABSTRACT: The current research aimed to verify the effects of erythropoietin (EPO) on vascular calcification under inflammatory conditions and the molecular regulator of vascular calcification induced by EPO. To induce vascular calcification and systemic chronic inflammation in SD rats, EPO was administered intraperitoneally, and 10% casein was injected subcutaneously. The administration period lasted for 20 consecutive weeks. Blood samples were subsequently collected to detect inflammatory factors and vascular calcification. Additionally, high-dose EPOs were applied to stimulate primary vascular smooth muscle cells (VSMCs), and vascular calcification was measured using alizarin red staining, alkaline phosphatase (ALP) activity, and calcium salt quantification. The probe 2', 7'-dichlorofluorescein diacetate (DCFH-DA) was employed to detect cellular reactive oxygen species (ROS) levels. The expressions of bone formation-related protein and anti-calcification protein matrix gla protein (MGP) were determined via Western blot. Compared with the control group, calcium deposits and vascular calcification were increased in the EPO group, tumor necrosis factor-alpha (TNF-α) group and TNF-α+ EPO group, whereas MGP was significantly reduced. Moreover, under the stimulation of TNF-α and EPO+TNF-α, pp38/p38 was increased substantially, the addition of p38 inhibitor SB203580 could significantly reduce calcium deposits and vascular calcification. In vivo experiment, compared with the EPO group, calcium salt deposition and vascular calcification were elevated in the EPO+casein group. The present results revealed that high-dose EPO could cause calcification of the abdominal aorta in rats. The inflammatory response aggravated the vascular calcification induced by EPO via activating p38 and ROS levels. Graphical Abstract: uf0001